Bioconversion of pomegranate residues into biofuels and bioactive lipids. (10th November 2021) - Dourou, Marianna; Economou, Christina N.; Aggeli, Lida; Janák, Miroslav; Valdés, Gabriela; Elezi, Nefeli; Kakavas, Dimitrios; Papageorgiou, Theodore; Lianou, Alexandra; Vayenas, Dimitrios V.; Certik, Milan; Aggelis, George
Abstract: Pomegranate residues (PRs), the solid residues comprising peels and seeds after juice extraction, are generated in abundance in Greece and contain a variety of carbon sources. Therefore, these residues can be regarded as a potential feedstock for chemical and biotechnological processes. The polysaccharides contained in PRs were extracted and hydrolyzed in a one-step process (not involving the use of chemical reagents), and the resulting broth was used as substrate in biotechnological applications, including ethanol and single cell oil (SCO) production. The yeasts Meyerozyma guilliermondii, Scheffersomyces coipomoensis, Sugiyamaella paludigena and especially Saccharomyces cerevisiae were able to efficiently convert reducing sugars derived from PRs into bioethanol. Ethanol production in static cultures (ensuring nearly anaerobic conditions) ranged from 3.6 to 12.5 g/L. In addition, the oleaginous yeasts Lipomyces lipofer and Yarrowia lipolytica as well as M. guilliermondii, S. coipomoensis and S. paludigena were tested for their ability to produce lipids suitable as feedstock for biodiesel production. Lipids were accumulated at concentrations up to 18% and were rich in palmitic and oleic acids. Finally, the oleaginous fungus Cunnichamella echinulata was cultivated on PR-based solid substrates for γ-linolenic acid (GLA) production. The fermented bio-products (i.e. fermented substrate plus fungal mycelia) contained up to 4.8 mg GLA/g of dry weight. Phenolic removal (up to 30%) was achieved by several of the above-mentioned microorganisms, including C. echinulata, L. lipofer, M. guilliermondii, S. paludigena and Y. lipolytica . In conclusion, the findings of this study demonstrate that PRs can be used as raw material for microbial growth, ethanol and SCO production, which is of economic and environmental importance. Graphical abstract: Image 1 Highlights: Pomegranate residues (PRs) are a suitable substrate for microbial fermentations. PR polysaccharide extraction and hydrolysis does not require the use of chemicals. PR hydrolysate is a suitable medium for yeast biomass and oil production. PR hydrolysate is a suitable medium for ethanol production. PRs mixtures with cereals can be used as substrate for solid state fermentation.